The Effect of Debt Policy, Investment Policy, Profitability on Company Value in Construction and Building Sub-Sector Companies Listed on IDX - Khairunnisa, Asyifa; Ardian, Noni (Journal of Community Research and Service, 2024)
This study aims to determine the effect of debt policy, investment policy, profitability on company value in construction and building sub-sector companies listed on the IDX from 2018-2022. The ratios used to measure debt policy are debt  to equity ratio (DER), investment policy is measured by price to earning ratio (PER), profitability is measured by return on assets (ROA), and company value is measured by price book value  (PBV). This research is a research with a quantitative approach. The sampling technique uses purposive sampling method. It is known that from 22 total populations, there are 13 companies that meet the criteria to be sampled.  Data analysis techniques using panel data regression analysis. The results showed that partially debt policy and investment policy did not affect the value of the company, but profitability affected the value of the company. The results also show that simultaneously debt policy, investment policy, and profitability affect the value of the company.